Energy analysis and modeling - Au, Chi Kwan (2010)
A cost-effective and efficient transportation sector is critical in improving Singapore’s economic competitiveness as well as standard of living for Singaporeans. Currently Singapore has an efficient and high standard land transportation system that can easily bring people and goods across the country. Other than just supporting other sectors of the economy, the transportation sector itself is also an important economic pillar. However, at the moment most of Singapore’s vehicles involve burning limited non-renewable energy, e.g. petrol and diesel. These non-renewable energy will deplete one day and it is therefore necessary to find the best cost effective and efficient way to use these energy, to sustain Singapore’s competitiveness.